TANGGUNGJAWAB HUKUM PERUSAHAAN ANGKUTAN UMUM TERHADAP KESELAMATAN PENUMPANG - Rielia Darma Bachriani; Irfan Cheetah Setiaaji (Universitas Karya Husada Semarang, 2023)
Transportation is a reciprocal agreement, in which the carrier binds himself to arrange the transportation of goods and or people from one place to another destination, while the other party is obliged to pay a certain amount of transportation costs. In the agreement for the transportation of people or passengers there are two legal subjects, namely the carrier and the passenger. Protection of passengers is the main obligation for the carrier itself. Several forms of safety guaranteed in Law Number 22 of 2009 for passengers, are protection for the safety of humans and/or goods. This study uses normative juridical techniques. The normative juridical method is used with secondary data to carry out an academic analysis of the safety of land public transport passengers. The conclusion of this study is that if an accident occurs and causes injury or death, the legal consequences for public transport companies are regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation in article 192 states that the public transport business entity is responsible for responsible for losses suffered by passengers who die or are injured due to the operation of transportation, except for an incident that cannot be prevented or avoided or due to the fault of the passenger.